Myopenia is associated with joint damage in rheumatoid arthritis: a cross‐sectional study. Issue 2 (30th January 2019) - Lin, Jian‐Zi; Liang, Jin‐Jian; Ma, Jian‐Da; Li, Qian‐Hua; Mo, Ying‐Qian; Cheng, Wan‐Mei; He, Xiao‐Ling; Li, Nan; Cao, Ming‐Hui; Xu, Dan; Dai, Lie
Abstract: Background: The link between body mass index (BMI) and disease characteristics in rheumatoid arthritis (RA) remains controversial. Body composition (BC) has been more frequently recommended to be used instead of BMI for more accurate assessment. Our study aimed to investigate the characteristics of BC in RA patients and their associations with disease characteristics. Methods: Body composition was assessed in consecutive Chinese RA patients and control subjects by bioelectric impedance analysis. Overfat was defined by body fat percentage (BF%) as ≥25% for men and ≥35% for women. Myopenia was defined by appendicular skeletal muscle mass index (ASMI) ≤7.0 kg/m 2 in men and ≤5.7 kg/m 2 in women. BMI and clinical data including disease activity, function, and radiographic assessment were collected. Active disease was defined by disease activity score in 28 joints with four variables including C‐reactive protein (DAS28‐CRP) ≥2.6. Functional limitation was defined as Stanford health assessment questionnaire disability index (HAQ‐DI) >1. Radiographic joint damage (RJD) was defined as the Sharp/van der Heijde modified sharp score (mTSS) >10. Results: There were 457 RA patients (mean age 49.5 ± 13.1 years old with 82.7% women) and 1860 control subjects (mean age 34.3 ± 9.9 years old with 51.2% women) recruited. Comparisons of BMI and BC between RA patients and control subjects in age and gender stratification showed that lower BMI with 17.7% underweight and lower ASMI with 45.1% myopenia are the main characteristics in RA patients. Compared with those without myopenia, RA patients with myopenia had significantly higher DAS28‐CRP (median 3.5 vs. 3.0), higher HAQ‐DI (median 0.38 vs. 0.13) with higher rate of functional limitation (24.8% vs. 7.6%), and higher mTSS (median 22.3 vs. 9.0) with more RJD (71.8% vs. 45.8%) (all P < 0.001). Multivariate logistic regression analysis showed myopenia were positively associated with functional limitation (OR = 2.546, 95% CI: 1.043–6.217) and RJD (OR = 2.660, 95% CI: 1.443–4.904). All RA patients were divided into four BC subgroups according to overfat and myopenia. Those with both overfat and myopenia had the worst disease characteristics. After adjustment for confounding factors, significant additive interactions were observed between overfat and myopenia in active disease (AP = 0.528, 95% CI: 0.086–0.971), functional limitation (AP = 0.647, 95% CI: 0.356–0.937), and RJD (AP = 0.514, 95% CI: 0.139–0.890). Conclusions: Myopenia is very common in RA patients that is associated with functional limitation and joint damage in RA. Further research on the underlying mechanism and the effect of skeletal muscle mass improvement in RA management are worth exploring in the future.